Pengaruh Penggunaan Gemini AI pada Perencanaan Proyek Biologi terhadap Kreativitas Peserta Didik di SMA : Penelitian - Rosi Ramadhani; Relsas Yogica; Zulyusri; Fitri Olvia Rahmi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
ThisPstudy waspconducted to determineethe extent to whichhthe use of Gemini AI in designing biology projects can influence student creativity in project-based learningm(PBL) at the highsschool level. Theeresearch method used was a quasi-experimentalmmodel with a Pretest-Posttest Control Group Design. The study population was all students of grade X PhasmE at SMA Negeri 1 Lubuk Alung. The sample consisted of two classes: X.E1 as the control group with 36 students, and X.E3 as the experimental group with 35 students. The research instrument was a creativity questionnaire. Data analysis was carried out using a t-test and obtained a significanceevalue of 0.02 which isssmaller than 0.05, indicating a significant difference between groups. In conclusion, the useeof Gemini AIlin the planning stage of biology projects has beenpproven topsignificantly increase student creativity.